People's Republic of China-Hong Kong Special Administrative Region : 2019 Article IV Consultation Discussions-Press Release; Staff Report; Staff Statement and Statement by the Executive Director for the People's Republic of China-Hong Kong Special Administrative Region. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with People's Republic of China-Hong Kong Special Administrative Region (SAR) discusses that the economy is projected to start recovering next year, but the pace is expected to be gradual and both near- and medium-term risks have increased significantly, including from trade and technology tensions, ongoing social unrest, and structural challenges of insufficient housing supply and high income inequality. Hong Kong SAR is well placed to address both cyclical and structural challenges with its significant buffers thanks to its long history of prudent macroeconomic policies. Given that the fiscal framework permits deficits during economic downturns, government spending should be increased significantly in the areas of social safety nets, education/retraining, and infrastructure to cope with the cyclical downturn and address structural challenges of insufficient housing and high-income inequality. This should be complemented with measures to ensure fiscal sustainability and greater equity.